The related factors on the preinternship scores and the exam result of Zahedan medical students in 2000 - Masoud Roudbari; Saeed Movahed (Kerman University of Medical Sciences, 2005)
Background: The preinternship (PI) exam is the most important examination of medical students which can assess their abilities in passing the general medicine Objective: To determine the effective factors on the preinternship score and result at Zahedan University of Medical Sciences Methods: The research was a crosssectional on 63 medical students participating in preinternship examinations in Zahedan University of Medical Sciences in 2000 The mean scores of basic sciences physiopathology clinical total and the scores of ten important courses of preinternship exam and the demographic variables were recorded and analyzed Results: The failing rate was 204% the relative risks of failing were 36 37 61 109 and 116 for the students with nondistrict group in quota system high age more than 55 year education period (to preinternship) with clinical score mean and total mean lower than the mean of all participants respectively and it was significant Also the mean of preinternship scores was significantly different based on marital status situation in quota system age education period A high correlation was observed between preinternship score and total scores mean physiopathology basic sciences and clinical scores respectively (079 075 073 and 073) Conclusion: Age quota system education period the clinical score mean infections diseases pharmacology and psychiatry scores are the most important factors influencing the exams results due to high and significant relative risks Marital status quota system age and education period cause the students taking part in a preinternship exam to get different means